Sibling Rivalry: Timbulnya Kecemburuan Sosial yang Disebabkan Oleh Perbedaan Gender atau Rentang Usia Kelahiran (Kasus Pada Usia 3-6 tahun) - Kamil, Nurhusni; Saputri, Indri Dewi; Zahrah, Faiqatuz; Mufida, Aina Yulifa'atun (Az-Zahra: Journal of Gender and Family Studies, 2024)
Competition between sibling relationships is inevitable. A little competition created between siblings is normal throughout the life span. This shows that the closeness between the two is close enough to give rise to many problems. However, this is not always good if it continues. Although in the end conflicts like this will disappear over time when each child reaches adulthood. Sibling rivalry starts from childhood. Every child who is not born as an only child will know about competition between siblings. This causes several changes in behavior towards a more negative direction. One of the negative attitudes produced by children is social jealousy between siblings which results in sudden and unusual changes in behavior. There are two factors that are generally known among the public, namely gender differences and birth age ranges. This research aims to find out and identify the factors that cause sibling rivalry in sibling relationships based on gender differences and birth age range. The type of research used in this research is qualitative research with a case study approach. The sample used in this study was 8 children with classifications, namely 4 pairs of children of the same gender and 4 pairs of children of different genders. The data collection technique used was in-depth and unstructured interviews submitted to each parent. For data analysis techniques using Miles and Huberman analysis techniques including data reduction, data display, and conclusion drawing/verification. The results of the research show that the problematic competition that occurs between siblings which causes social jealousy is caused by the close birth age range between one child and another. This is the cause of social jealousy that often occurs between sibling relationships. So arguments often easily arise over trivial things.